Microbial synthesis of branched-chain β,γ-diols from amino acid metabolism - Peiling Wu; Haofeng Chen; Yueyang Chen; Yang Zhang; Jifeng Yuan (Nature Communications)
Abstract Microbial synthesis of chemicals using renewable feedstocks has gained interest due to its sustainability. The class of β,γ-diols has unique chemical and physical properties, making them valuable for diverse applications. Here, we report a biosynthetic platform in Escherichia coli for the synthesis of branched-chain β,γ-diols from renewable feedstocks. Firstly, we identify an acetohydroxyacid synthase from Saccharomyces cerevisiae to catalyze the condensation of branched-chain aldehydes with pyruvate, forming α-hydroxyketones. Next, de novo production of branched-chain β,γ-diols (4-methylpentane-2,3-diol, 5-methylhexane-2,3-diol and 4-methylhexane-2,3-diol) is realized from branched-chain amino acids (BCAA) metabolism. After systematic optimization of the BCAA pathway, we have achieved high-specificity production of 4-methylpentane-2,3-diol from glucose, achieving 129.8 mM (15.3 g/L) 4-methylpentane-2,3-diol with 72% of the theoretical yield. In summary, our work demonstrates the synthesis of structurally diverse branched-chain β,γ-diols, highlighting its potential as a versatile carbon elongation system for other β,γ-diol productions.